Pola Hidup dan Dukungan Keluarga Berhubungan dengan Rutinitas Hemodialisa pada Pasien Gagal Ginjal Kronik : Lifestyle and Family Support are Associated with Hemodialysis Adherence in Chronic Kidney Failure Patients - Utami, Novianty; Weslei Daeli; Susaldi (MPI Press, 2022)
Introduction: Kidney disease has a major effect on global health, both as a direct cause of global morbidity and mortality and as an important risk factor for cardiovascular disease of the heart and blood vessels. CKD is largely treatable so it deserves greater attention for decision-making for patients and families in undergoing a course of therapy. Objective: To determine the relationship between lifestyle and family support with routine hemodialysis in patients with chronic kidney failure at Ciawi Hospital, Bogor. Methods: The research design used is a descriptive correlation. The research population was all respondents in Ciawi Hospital, Bogor. By using a total sampling technique of 72 people. The instrument used a questionnaire and the analytical tool used was the Spearman rank correlation. Results: The results showed that most of the patients with chronic kidney failure who underwent hemodialysis in the Hemodialysis room at the Ciawi Hospital, Bogor were male as many as 38 respondents (52.8%), ages 44-45 as many as 34 respondents (47.2%), SMA education was 46 respondents (63.9%), and occupations with other categories were 27 respondents (37.5%). The pattern of life with routine hemodialysis implementation at Ciawi Hospital Bogor is good for as many as 49 respondents (68.1%) and there is family support for as many as 48 respondents (66.7%) so there is a relationship between lifestyle and family support with hemodialysis routines at Ciawi Hospital, Bogor with P-value = 0.016 and OR 9.4 for lifestyle relationships, while P-value = 0.022 and OR 10.1 for family support. Conclusion: There is a relationship between lifestyle and family support with the implementation of hemodialysis in patients with chronic kidney failure in the Hemodialysis Room of Ciawi Hospital, Bogor Regency. Lifestyle has a greater influence on the suitability of the hemodialysis schedule.